Special education in higher education: contributions and perspectives - Doracina Aparecida de Castro Araujo; Carla Cristina Castro Araujo; Elson Luiz de Araujo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
With the advent of special education in Brazil boosted by the Salamanca Declaration (1994), some theoretical positions presented themselves, such as the full inclusion of persons with disabilities in ordinary schools and the inclusion from the look from the perspective of the development of higher psychological functions (VYGOTSKY, 1997). In addition, there are other theoretical positions and intermediate educational practices aimed at organic conditions of students with disabilities and to the possibilities of integration of those more committed in relation to disability in specialized education centers. From these considerations is that aims to understand the contributions of the authors of 12 articles of the Brazilian Journal of Special Education (RBEE) on special education in higher education, as well as the prospects for the students of special education target audience (PAEE) that enters the higher education. The qualitative approach, from the perspective of Cultural-historical. Psychology, has guided the analysis of these RBEE productions, in the period from 2010 to 2014. As a result it was found that the students who reach the PAEE higher education face difficulties through veiled prejudice, physical accessibility, inadequate curriculum, among others. It can be concluded that the inclusion of students PAEE lacks attention, since Kindergarten, with educational work guided in developing their higher psychological functions, so you can overcome the barriers located at all levels of schooling, so as to contribute to not only reach to higher education, but also (and especially) that come out with knowledge.